Assembly-level analyses of an innovative long-life marine SMR loaded with accident tolerant fuel. (November 2019) - Li, Xuezhong; Cai, Jiejin; Li, Zhifeng; Liu, Shichang; Tang, Zhihong
Highlights: Assembly-level analyses of a long-life marine SMR loaded with ATF is performed. The new assembly is designed and its burn-up reaches to 95 MWD/KgU. The new design is proved to be safe with negative FTC and MTC. Accident Tolerant Fuel/Cladding is implemented and it performs well. Abstract: A call for flexible power generation for a wide range of applications is gradually increasing, making Small Modular Reactor (SMR) a heat topic, especially for marine power. Unlike normal reactors, marine reactors demand a long lifetime up to 15 years without refueling, a high power-density and also a higher reliability and security. The standard PWR cannot achieve this goal. Here, a new 13 × 13 assembly loaded with Accident Tolerant Fuels (ATFs): U3 Si2 – FeCrAl system, is proposed and analyzed on an assembly-level. U3 Si2 is one kind of ATFs with high heavy metal density and thermal conductivity. It has a lower parasitic absorption. FeCrAl has a great radiation resistance, corrosion resistance and thermodynamic properties although with serious neutron penalties. It is currently the fastest researched accident tolerant cladding material. The fuel enrichment of this assembly is raised to 13%, prolonging the burnup to up to 95, 000 MWD/tU, which means that the reactor can survive for more than 15 years at its rated power density. Using 15 B4 C control rods can help achieve the beginning-of-life cool shutdown (K < 0.95). The power of the assembly is well distributed during the whole burnup. In consider of the inherent safety of reactor operation, the reactivity coefficients, especially Fuel Temperature Coefficient (FTC) and Moderator Temperature Coefficient (MTC) are computed and proved to be negative values, forming a negative feedback effect. The preliminary design is well-pleasing and it may be a better choice for future marine SMRs.